Handbook of food analysis. - Nollet, Leo M. L., 1948- (New York : Dekker, 2004)
This three-volume handbook supplies food chemists with essential information on the physical and chemical properties of nutrients, descriptions of analytical techniques, and an assessment of their procedural reliability. Volume 3 explores the usage and results of chemometrics, differential scanning calorimetry, chromatographic and electrophoretic techniques, DNA- and protein-based analyses, and cutting-edge methods utilizing biosensors and nanoscale analytical systems. Attuned to contemporary food industry concerns, the third volume also features new, topical coverage of the analysis of meat quality and the quantification of genetically modified organisms in food.
Dl.3: Methods and instruments in applied food analysis.
Keywords: Voedingsmiddelenonderzoek